Influence of Response-Option Combinations when Measuring Sense of Efficacy for Teaching: Trivial, or Substantial and Substantive? - Trevethan, Robert; Ma, Kang (Frontiers in Education, 2021)
Certain combinations of numbering and labeling of response options on Likert scales might, because of their interaction, influence psychometric outcomes. In order to explore this possibility, two versions of a scale for assessing sense of efficacy for teaching (SET) were administered to preservice teachers. One version had seven response options with labels at odd-numbered points; the other had nine response options with labels only at the extremes. Before outliers in the data were adjusted, the first version produced a range of more desirable psychometric outcomes but poorer test–retest reliability. After outliers were addressed, the second version had more undesirable attributes than before, and its previously high test–retest reliability dropped to poor. These results are discussed in relation to the design of scales for assessing SET and other constructs as well as in relation to the need for researchers to examine their data carefully, consider the need to address outlying data, and conduct analyses appropriately and transparently.